Karakteristik Kurikulum KTSP, Kurikulum 2013 dan Kurikulum Merdeka Perspektif Kurikulum Terpadu di Sekolah Dasar - Syahrani Jefri, Ghina; Gusmaneli, Gusmaneli; Handayani, Zaskia (UNIVERSITAS SERAMBI MEKKAH, 2025)
This paper discusses a comparison of three curricula that have been and are being implemented in Indonesia, namely the KTSP Curriculum, the 2013 Curriculum, and the Merdeka Curriculum. The discussion and description are based on the theoretical framework of integrated learning models developed by Fogarty (1991) in which there are ten ways or models for planning integrated learning. The ten ways or models are: (1) fragmented, (2) connected, (3) nested, (4) sequenced, (5) shared, (6) webbed, (7) threaded, (8) integrated, (9) immersed, and (10) networked. The purpose of this research is to compare the characteristics and determine what curriculum is most suitable to be implemented in elementary schools. The research method used is library research or literature study by reviewing various literature relevant to our discussion. The results of the study show that the KTSP Curriculum applies the Fragmented learning model, while the 2013 Curriculum and the Merdeka Curriculum apply the integrated learning model. In a comparison of the three curricula regarding suitability for elementary school level learning, our group is of the opinion that the appropriate curriculum is Independent Curriculum.